COVID-19 in LAC : High Frequency Phone Surveys - Technical Note - Mejía-Mantilla, Carolina; Olivieri, Sergio; Rivadeneira, Ana; Lara Ibarra, Gabriel; Romero, Javier (World Bank, Washington, DC, 2021)
Latin American and the Caribbean is one of the regions in the world most affected by the COVID-19 pandemic, and the welfare impacts for households have been severe. At the macroeconomic level, the World Bank estimates a contraction of 6.9 percent of the region’s GDP in 2020, due to pandemic-control measures and the deceleration of the global economy (World Bank, 2021). Regional export prices significantly dropped in the first semester of 2020 (5.2 percent) (Inter-American Development Bank, 2020), and although they began to recover in the second half of the year, the volume of goods-exports dropped by 8 points by the third quarter of 2020 (World Bank, 2021).